Pengembangan aplikasi mobile untuk memfasilitasi pencarian buku di smart library - Kusumaningtyas, Juwita Artanti; Permana, Zaky Renald Putra (Librarium: Library and Information Science Journal, 2025)
The development of a mobile application to facilitate book searches in smart libraries aims to improve efficiency and convenience in accessing library services. This application allows users to search for books, check availability, and borrow them digitally via mobile devices. Additionally, the application can provide personalized book recommendations using technologies such as RFID, GPS, and artificial intelligence (AI). By automating the borrowing and returning process, the system not only enhances user satisfaction but also supports the modernization of libraries. Studies show that mobile library applications can expedite information access, improve operational efficiency, and support digital transformation in library management.